Obese-insulin resistance accelerates and aggravates cardiometabolic disorders and cardiac mitochondrial dysfunction in estrogen-deprived female rats - Sivasinprasasn S. (Springer Netherlands, 2015)
© 2015, American Aging Association. Women have a lower incidence of cardiovascular diseases (CVD) than men at a similar age but have an increased incidence of CVD and metabolic syndrome after menopause, indicating the possible protective effects of estrogen on cardiometabolic function. Although obesity is known to increase CVD risks, its impact on the heart on estrogen deprivation is still inconclusive. We investigated the effects of obese-insulin resistance on cardiometabolic function in estrogen-deprived ovariectomized rats. Adult female ovariectomized (O) or sham (S)-operated rats randomly received either normal diet (ND, 19.77 % fat) or high-fat diet (HF, 57.60 % fat) (n = 6/group) for 12 weeks. The heart rate variability (HRV), left ventricular (LV) performance, cardiac autonomic balance, cardiac mitochondrial function, metabolic parameters, oxidative stress, and apoptotic markers were determined at 4, 8, and 12 weeks. Insulin resistance developed at week 8 in NDO, HFS, and HFO rats as indicated by increased plasma insulin and HOMA index. However, only HFO rats had elevated plasma cholesterol level at week 8, whereas HFS rats had showed elevation at week 12. In addition, only HFO rats had depressed HRV, impaired LV performance indicated by decreased fractional shortening (%FS) and cardiac mitochondrial dysfunction indicated by increased mitochondrial ROS level, mitochondrial depolarization and swelling, as early as week 8, whereas other groups exhibited them at week 12. Either estrogen deprivation or obesity alone may impair metabolic parameters, cardiac autonomic balance, and LV and mitochondrial function. However, an obese insulin-resistant condition further accelerated and aggravated the development of these cardiometabolic impairments in estrogen-deprived rats.